Revisiting Bhabha’s Mimicry in George Orwell’s Animal Farm - Ruly Indra Darmawan (Pioneer: Journal of Language and Literature, 2020)
This paper talks about Bhabha’s Mimicry’s idea in Orwell’s novel entitled Animal Farm. Postcolonialism theory is used to analyze the Animal Farm since the novel portrays the dynamic of animals’ lives after being freed from human colonization. Bhabha’s mimicry is utilized to demonstrate Napoleon and his pig family as the principal data that portrays animals that are imitating a human as a result of human’s colonization. The animal is known as the foe of humankind on the ranch that they live. Mimicry ideas utilized are Bhabha’s both ambivalence and term the same but not quite. Those ideas are practised to uncover the pig’s propensity and act that represents postcolonial discourse. The mimicry in Animal Farm begins with Old Major’s discourse that is contaminating all animals on the ranch with his feeling of inadequacy towards the man. It results in another form of colonization directed to the animals as the colonized.